Creatively re-mediating the integration of visual resources with spoken expositions during slideshows in undergraduate psychology lectures - Hallewell, Madeline Jennifer (2013)
The research describes the communicational practices of HE lectures employing a PowerPoint slideshow in order to examine the multimodal dynamic of this genre for exposition. Based on pragmatist conceptions of learning and theories of visual/ verbal processing, the research explored how different slide-elements were integrated with lecturers’ speech, and how this integration related to students’ engagement. A two-stage mixed method investigation collected video-recordings of 22 lectures and interviews with 9 lecturers. Additionally, focus groups were carried out with 37 students, and copies of their lecture notes were made and analysed. Using the resulting data, three separate empirical studies revealed; 1) Two characteristic speech-slide relationships were associated with the extent and explicitness of speech-slide integration. In the “referent” relationship, the lecturer addresses and comments on slide-text, and in the “scaffolding” relationship, the slide-text serves to structure their speech. 2) The relationship employed depended on lecturer intentions for the slide-lecture, which predominantly involved elaboration of the lecture outline. Consequently, students regarded slide-text as lecture notes, and expected it to be addressed consistently and explicitly. Owing to their focus on recording the slide-text and accompanying explanation, there was shown to be little opportunity for meaningful interaction with the slide-lecture. 3) Visual elements have the potential to engage students in a meaningful interaction, yet integration of them by lecturers revealed that they were not often exploited to such ends. It is concluded that the integration of text in slide-lectures presents little opportunity for achieving a fully engaging lecture experience. Although visual elements offer a promising alternative, little is known about how text or visuals can best be integrated with speech to this end. Thus slide-lectures might be more pedagogically profitable if lecturers are better informed about how their integration can be used to invite students to engage with evidence on screen. This thesis contributes towards knowledge about such integration.